2019
DOI: 10.1177/0262489319873642
|View full text |Cite
|
Sign up to set email alerts
|

The influence of blowing agent addition, talc filler content, and injection velocity on selected properties, surface state, and structure of polypropylene injection molded parts

Abstract: The effects of blowing agent, talc, and injection velocity on properties of polypropylene molded parts were presented. Blowing agent was dosed to plastic in amounts 1–2% and talc 10–20%. The results of selected properties, such as weight, thickness, hardness, impact strength, tensile strength, and gloss, were presented. The article also presents microscopic investigations. The blowing agent and talc content have a large impact on mechanical properties and gloss of parts than addition of blowing agent. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…The research revealed that with the increasing talc content, changes to the measured mechanical parameters were observed. On the other hand, increasing talc concentration caused an increase in the hardness up to some point (6 or 9 wt.%), after which its decrease was noticed [48,49]. The appearance of this type of dependence is explained by the uneven distribution of the filler, as the filler type and its distribution are the most important factors affecting the mechanical properties of PP/talc compounds [48].…”
Section: Resultsmentioning
confidence: 99%
“…The research revealed that with the increasing talc content, changes to the measured mechanical parameters were observed. On the other hand, increasing talc concentration caused an increase in the hardness up to some point (6 or 9 wt.%), after which its decrease was noticed [48,49]. The appearance of this type of dependence is explained by the uneven distribution of the filler, as the filler type and its distribution are the most important factors affecting the mechanical properties of PP/talc compounds [48].…”
Section: Resultsmentioning
confidence: 99%
“…Polymers and Fillers Molded Part Thickness, mm [4,7,8,11,13,16,22,23] PP GF20; PP/LDPE blends; PP + GF + Talc; PP-TPU; PP CF20; PP CF30; PP + EPDM + TALC 2.4-4.0 [6,9,15,17] PA66 GF 30 1.5-4.0 [7,24] PLA/PHBV; PLA/PTFE (fibril) 3.3-4.0 [10,12] PC; PC/ABS 1.7-4.0 [14,25] PS 3.0…”
Section: Entry In the Literature Listmentioning
confidence: 99%
“…Their addition also affects the processing of the polymer [7]. The filler can be introduced into the polymer by various methods including melt-mixing [8], melt extrusion [9], and injection molding [10]. Mineral fillers for thermoplastics often include natural sedimentary rocks, like calcium carbonate [11], mica, clinoptilolite [12], zeolites [13], kaolin [14], silica [15], titanium dioxide [16] or diatomaceous earth [17], and clay minerals with a two-layer structure (kaolin-serpentine group) or three-layer structure (talc-pyrophyllite group, mica group, etc.)…”
Section: Introductionmentioning
confidence: 99%